What Influences Fashion Consumers’ Loyalty On Social Media in Indonesia? - Golan Hasan; Eva Noor Liana (International Journal of Islamic Business and Management Review, 2022)
This research examines the determining factors which can affect consumer loyalty for fashion products on social media mediated by purchase intention. This research focuses on both locally produced and imported fashion products sought after by Batam City residents. Collected data is pooled from 352 respondents using Google Forms. The questionnaires were taken from the works of Abou Ali et al., (2021) dan Prasad et al., (2019). The causal-comparative quantitative approach is used in this research, while linear regression is used to prove the relationship between each hypothesis. This research shows that the relationship between country of origin, customer engagement, influencer marketing, purchase intention, and trust can explain about 53% of customer loyalty. Meanwhile, perceived value does not significantly affect customer loyalty directly. To examine the mediating relationship of purchase intention, this research uses the aforementioned variables to be compared. The result shows that there is a mediating relationship between purchase intention and independent perceived value and trust. Altogether this research is conducted in a relatively short time. Additionally, the lack of supporting journals and sources that can reinforce the mediating relationship of purchase intention toward perceived value and trust makes this study not thoroughly discussed.